2012
DOI: 10.1097/bot.0b013e318220edae
|View full text |Cite
|
Sign up to set email alerts
|

Locking Plates in Osteoporosis

Abstract: Locking plates were shown to provide improved mechanical performance over nonlocking plates in torsional cyclic loading in a osteoporotic cadaveric fracture model. Our results confirm general conclusions of previous work that used a synthetic bone model of osteoporosis, but we found a high rate of catastrophic failure, questioning the validity of the previously published synthetic model of osteoporosis (overdrilling of synthetic bone) for this application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Locking constructs can overcome this disadvantage because stability is achieved through the locking interface between pate and screws and therefore it has been suggested that they are ideal for the treatment of osteoporotic fractures [711]. Cadaveric studies have also demonstrated that locking plates have an improved mechanical performance in torsional cycling loading over nonlocking constructs, especially in osteoporotic bone [12]. …”
Section: Discussionmentioning
confidence: 99%
“…Locking constructs can overcome this disadvantage because stability is achieved through the locking interface between pate and screws and therefore it has been suggested that they are ideal for the treatment of osteoporotic fractures [711]. Cadaveric studies have also demonstrated that locking plates have an improved mechanical performance in torsional cycling loading over nonlocking constructs, especially in osteoporotic bone [12]. …”
Section: Discussionmentioning
confidence: 99%
“…More recently, humeral nails have been designed with threaded screw holes in order to provide more stability. Locking plates are theoretically advantageous in osteoporotic fractures, supplying a wider fixing area [33][34][35][36] .…”
Section: Special Consideration For Osteoporosismentioning
confidence: 99%
“…Numerous biomechanical studies have demonstrated the mechanical superiority of locking fixation in a fracture model but none have focused on fixation of the bone scaffolds. [18][19][20] We hypothesized that the locking plate fixation provides more stable internal fixation under cyclic axial, bending, and torsional loading. The study is clinically relevant in that it will guide treating surgeons with respect to internal fixation and guide post-operative regimens for the patients with massive intercalary skeletal defects treated with bone scaffolds.…”
Section: Segmental Allografts Have Been Advocated To Reconstruct Defementioning
confidence: 99%